Estimation of state of charge (SoC) in rechargeable batteries - Yuan, Yalin. (2012)
State of Charge (SoC) corresponds to the stored charge available in a battery to do work relative to that which is available after the battery has been fully charged. The SoC is routinely used to describe the performance of a cell and is needed not just for providing the `Fuel Gauge’ indication, but also for control unit to ensure optimum control of the charging, discharging balancing processes. The SoC of each individual cell can be used to verify that the cell does not become overstressed. Besides, the SoC is also used to determine the end of the charging and discharging cycles. So it is a critical state variable in optimizing the operation of a battery pack and protecting the cells, as well as providing a reliable and “transparent” driving experience in the context of hybrid-electric-vehicles (HEV).